Assessment of fission product inventory considering axial burnup of a fuel assembly. (April 2016) - Jeong, Hae Sun; Jeong, Hyo Joon; Kim, Eun Han; Han, Moon Hee; Hwang, Won Tae
Highlights: We analyze the fission product inventory based on the axial burnup of fuel. This reflects the accident occurrence cycle and fuel meltdown at BOC, MOC, and EOC. SCALE is used for the burnup cross-section generation and depletion calculations. CASE (I) scenario is applied with an average burnup for a general assumption. CASE (II) considers accident occurrence cycle and the degree of fuel meltdown. Abstract: The fission product inventory for a loss-of-coolant accident (LOCA) analysis is generally evaluated based on the average burnup of the fuel at the end of life regardless of the variation of the actual burnup with time. In this study, we analyze the variation of the fission product inventory based on the accident occurrence cycle and the degree of fuel meltdown, which reflect the axial burnup of the fuel at the beginning, middle, and end of the cycle (BOC, MOC, and EOC). The fuel assembly for the Hanul unit 6, which is an OPR1000-type pressurized water reactor (PWR) in Korea, was chosen as an analysis model for the source-term assessment. The burnup cross-section library was generated using the TRITON module of the SCALE6.1 code system, and the depletion calculations were carried out using ORIGEN-ARP. The first scenario, which is referred to as CASE (I), is applied with an average burnup at the EOC, which is a commonly recommended conservative assumption in accident analyses. The CASE (II) scenario includes various cases that consider the accident occurrence cycle and fuel meltdown from the top to the bottom of the core at the BOC, MOC, and EOC. As a result, the inventory of the main nuclides gradually decreased as the reactor core operation was performed. In addition, the activity intensity for the main fission products of CASE (II) was shown to be higher than that of CASE (I) in the range above a fuel meltdown of approximately 30%. Therefore, this study concludes that not all of the results obtained by the CASE (I) assumption are guaranteed to be more conservative than those obtained by CASE (II).